Pengaruh Pemberian Dosis Biochar Tempurung Kelapa Terhadap Pertumbuhan dan Hasil Tanaman Sawi Pakcoy (Brassica rapa L.) - Komang Dean Ananda; Putu Lasmi Yuliyanthi Sapanca; Ni Putu Eka Pratiwi; Dionisius Agung Elo (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Pakcoy plant is a vegetable plant that is in great demand by people in Indonesia because it has nutritional value, contains fiber, vitamins A, B, B2, B6, and C, calcium, phosphorus, copper, magnesium, iron, and protein. high economy. Currently, many agricultural lands in Indonesia are in very poor condition, because they are damaged and poor in nutrients. One of the main causes is due to the use of inorganic (non-biological) fertilizers, which do not pay attention to the dosage or are excessive. This study used a randomized block design (RBD) method with 5 treatments, namely treatment with a dose of biochar 100 g/10 kg of soil (B1), a dose of biochar of 150 g/10 kg of soil (B2), a dose of biochar of 200 g/10 kg of soil (B3). , the dose of biochar is 250 g/10 kg of soil (B4), the dose of biochar is 300 g/10 kg of soil (B5). Each treatment was repeated four times so that all treatments became 20. The results showed that the application of coconut shell biochar 200 g/10 kg of soil gave the best growth results for all parameters observed